Molecular identification and artificial cultivation of a wild isolate of oyster mushroom in Albania - Jordan Merkuri; Stefania Mirela Mang; Ippolito Camele; Magdalena Cara; Gian Luigi Rana (Italian Journal of Agronomy)
Basidiomata of a wild mushroom macroscopically recognised as Pleurotus ostreatus were observed on an oak trunk in a mixed wood of northern Albania. Pure cultures of the fungus were then obtained on potato-dextrose-agar medium. Molecular analyses of genomic DNA of the fungus confirmed its identification. The rDNA ITS region nucleotide sequence of the studied Pleurotacea matched at 99% those of two P. ostreatus strains already present in NCBI GenBank database. The rDNA ITS nucelotide sequences of two pure cultures of the Albanian P. ostreatus were deposited in EMBL database under the accession numbers LN849458 and LN849459. One of the fungus isolates was subsequently cultivated under protected and semi-natural conditions. Productivity and biological efficiency of the Albanian P. ostreatus ranged from about 10% to 16% and from 33 to 53.33%, respectively. This seems to be the first report on the artificial cultivation of P. ostreatus in Albania and could have, in the next future, a high economic impact on development and diffusion of this important edible mushroom over the country.